Rapid detection of the positive side reactions in vanadium flow batteries. (1st January 2017) - Liu, Le; Li, Zhaohua; Xi, Jingyu; Zhou, Haipeng; Wu, Zenghua; Qiu, Xinping
Graphical abstract: Highlights: A method for rapid measurement of the positive side reactions in VFB is presented. The SOC of positive electrolytes can be detected with resolution of 0.002%. Side reaction ratios at different charge currents, flow rates are obtained. Abstract: We present an optical detection method for rapid measurement of the positive side reactions in vanadium flow batteries (VFB). By measuring the transmittance of the positive electrolytes in VFB, the states of charge (SOC) of the positive electrolytes can be detected at very high resolution (better than 0.002% in the SOC range from 98% to 100%), due to the nonlinear transmittance spectra caused by the interactions between V(IV) and V(V) ions. The intensity of the positive side reactions of a VFB can be rapidly measured by a few steps, attributing to the fact that the positive side reactions occur only during the high voltage charging process. The ratios of the positive side reactions at different charge currents and different flow rates are obtained while causing no damage to the battery. This optical detection method can rapidly determine the optimal parameters of the VFB system, providing new means for studying the electrochemical reactions in the VFB system and rapid test in industrial production of VFBs.